Tennis flat forehand drive stroke analysis: three dimensional kinematics movement analysis approach - Rusdiana, Agus (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
The purpose of this study was to analyze the ability of the flat forehand drive stroke with a three-dimensional kinematics analysis approach in tennis. The method used was quantitative descriptive, while the subjects were 18 male tennis players (age 27 ± 3.7 years, height 169 ± 7.4 cm, body weight 71.5 ± 8.3 kg). This instrument uses three video cameras, one set of calibration, motion analysis software, manual markers and a radar speed gun. The results of this study showed that of the shoulder internal rotation, wrist flexion, trunk and hip rotations for players who have skills shows greater results when compared to the novice players. In addition, the skills player group produce ball speed that is greater than the novice players. The results of this study concluded that the series of motion starting from the hip joint rotation, the maximum external-internal shoulder rotation contributed greatly to the racket speed in generating greater ball momentum. Meanwhile, the shoulder internal velocity is the key to producing the racket maximum speed. The recommendation from the results of this study for further research is to compare the performance of forehand and backhand strokes in the elite group with a three-dimensional analysis approach.